CHARACTER EDUCATION AND SOCIAL PROBLEMATICS OF COMMUNITY - Jaedi, Jaedi; Zaenudin, Zaenudin; Edi, Sarwo (Riviera Publishing, 2023)
Character education is an education system that aims to instill certain character values in society which includes components of knowledge, awareness or will, as well as actions to implement community education values in realizing the life of the nation by instilling character education. This research aims to identify and improve relevant character values in society. This research uses a qualitative case study type with data analysis methods. This research was conducted in Indramayu Regency using Indramayu Regency Strategic Plan study materials and the 2020 Indramayu Figures book. Pure Enrollment Rates (APM) and Gross Enrollment Rates (APK) According to Level of Education in Indramayu Regency in 2019 and 2020 at SMA/SMK/MA is 69.79. Even though there has been an increase in the Education Human Development Index (HDI) in Indramayu Regency since 2008, the School Enrollment Rate (APS), Net Enrollment Rate (APM), and Formal Gross Enrollment Rate (APK) are still low. The low level of education at this age is a problem in the human development index.